2006
DOI: 10.1103/physreve.73.051911
|View full text |Cite
|
Sign up to set email alerts
|

Model of low-pass filtering of local field potentials in brain tissue

Abstract: Local field potentials (LFPs) are routinely measured experimentally in brain tissue, and exhibit strong low-pass frequency filtering properties, with high frequencies (such as action potentials) being visible only at very short distances (≈10 µm) from the recording electrode. Understanding this filtering is crucial to relate LFP signals with neuronal activity, but not much is known about the exact mechanisms underlying this low-pass filtering. In this paper, we investigate a possible biophysical mechanism for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 19 publications
6
120
0
1
Order By: Relevance
“…measurements. A previously suggested mechanism for the relatively small low-pass filter effect observed in vivo is the polarization of cell membranes (11). With the disintegration of cell membranes after death, it is conceivable that the filtering effect is further diminished, leading to the flattened frequency response.…”
Section: Discussionmentioning
confidence: 99%
“…measurements. A previously suggested mechanism for the relatively small low-pass filter effect observed in vivo is the polarization of cell membranes (11). With the disintegration of cell membranes after death, it is conceivable that the filtering effect is further diminished, leading to the flattened frequency response.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most previous studies, however, we found that low-frequency LFPs (in the 1-8 Hz range) were equally highly informative about the movie. The previously reported lack of visual stimulus selectivity at low LFP frequencies was commonly ascribed to the hypothesis that cortex acts as capacitive filter, spatially blurring low-frequency signals, which travel longer distances than those at high frequencies (Bedard et al, 2006). The hypothesis of capacitive filtering proved wrong according to recent detailed measurements of the cortical impedance spectrum (Logothetis et al, 2007).…”
Section: Temporal Scale Of the Lfp And Spiking Signalmentioning
confidence: 99%
“…However, it has been shown by Molden et al (2013) that to obtain an accurate action potential waveform, it is imperative to record signals with frequencies as low as 12.5Hz. Further, for local field potentials -which are extracted by low-pass filtering below 250Hz (Buzsáki et al, 2012;Oweiss, 2010;Bedard et al, 2006) -this approach completely fails in removing powerline noise. Band-stop filters have been used to attenuate powerline noise to inconspicuous levels.…”
Section: Introductionmentioning
confidence: 99%